IFNγ-mediated suppression of alternative NF-κB in tumor-resident myeloid cells promotes selective recruitment of cytotoxic but not regulatory T cells - Brinkman, Adam; Muthuswamy, Ravikumar; Dong, Bowen; Edwards, Robert P.; Kalinski, Pawel (Frontiers in Immunology, 2025)
Immunotherapy is currently effective in less than half of patients with solid tumors, and most responders develop secondary progression. High infiltration of the tumor microenvironment (TME) with CD8+ cytotoxic T cells (CTLs) and low infiltration with regulatory T cells (Treg) predicts the patients’ responses to immunotherapy and long-term outcomes. To identify the mechanisms regulating long-term stability of CTL infiltration, we analyzed the impact of CTL-produced cytokines on the TME by co-culturing patient-isolated ascites cells with activated T cells. Unexpectedly, we observed that activated CTLs selectively induce cytotoxic T cell-attracting chemokines but not chemokines that attract T regulatory cells in ovarian cancer TME and tumor-associated myeloid cells, resulting in recruitment of additional CTLs without Tregs. This selectivity resulted from the unique dependence of CCL22 induction on both canonical and alternative NF-κB and the suppression of alternative NF-κB signaling by T cell-released IFNγ. Our data demonstrate that T cell-produced IFNγ suppresses alternative NF-κB signaling in TME-associated myeloid cells, allowing for the induction of CTL-attracting chemokines with the concomitant suppression of Treg-attracting CCL22. These novel functions of IFNγ and activated T cells in regulating the balance between canonical and alternative NF-κB signaling in myeloid cells provide new opportunities to enhance and stabilize the selective CTL influx in the TME.